The assessment algorithm for sustainable development goals in the Hukiv, Dereluy, and Vyzhenka river basin systems of Chernivtsi oblast - Kyryliuk, Serhii (Iasi, 2021)
The study deals with an integral assessment of hydromorphological and geoecological conditions of the Hukiv (flatland type of river), Dereluy (foothill type of river), and Vyzhenka (mountainious type of river) river basin systems. The indicators characterizing the river basin in the best way as a holistic system, the channel, floodplain, and watershed altogether, in natural reference conditions and in terms of human economic activity are addressed.
Keywords: sustainable development; The assessment algorithm; Hukiv; Dereluy; Vyzhenka